(untitled) (Revista Lusófona de Educação, 2025)
This text presents and discusses the results of an investigation into Social Representations (SR) and Social Pedagogy, developed with a group of social educators in training in Rio de Janeiro, Brazil. The SR are present in the formative processes of all social educators and unfold in the organization of their daily practices. The main objective was to understand how the SR contribute to the conditioning of the formative processes of social educators, framed by Social Pedagogy understood as a specific educational science guided by the principle of hospitality. The research, exploratory, descriptive, and qualitative in nature, involved the analysis of the formative activities of 26 social educators between the years 2023 and 2024. The results showed the existence of SR of "teacher training" anchored in the figurative nucleus "School". The developments of these SR were: the silencing of the discussion about Social Education as an autonomous area of the school phenomenon; the difficulty in understanding the demands of the socio-educational context; and the exclusion of the educational-other as a parameter of socio-educational practices. These results suggest the need to develop and reaffirm the specific contents of Social Pedagogy, particularly the notion of hospitality in the formative processes of social educators, in order to reduce the deviations caused by SR. Keywords: Social Pedagogy; Social Representations; Training; Social Educators; Hospitality